College students' experiences of hedonia and eudaimonia in their everyday activities: Degrés d'hédonisme et d'eudémonisme éprouvés par des étudiants du niveau universitaire au fil de leurs activités quotidiennes. (February 2018) - Atler, Karen E.; Eakman, Aaron M.; Orsi, Rebecca
Background: Experiences of hedonia (i.e., seeking pleasure) and eudaimonia (i.e., actualizing human potential in pursuit of meaningful goals) are central to the study of human well-being. Purpose: This study sought to examine levels of hedonia (pleasure) and eudaimonia (productivity) in a convenience sample of college (university) students' ( n = 264) daily activities, controlling for levels of perceived stress. Method: Data were gathered using a 24-hr time-use recall diary designed to assess objective and subjective information about everyday activities. Descriptions of self-reported everyday activities were coded into 20 activity types. Findings: Activities reported high in pleasure were eating, listening to music/watching movies, and exercise. Activities reported as high in productivity were studying and working. Activities reported as high in both pleasure and productivity were reported less frequently and often had a recognizable outcome or provided social connection. Implications: Developing a greater understanding of how college students experience their daily activities could strengthen programs designed to enable students to manage stress and sustain their well-being.